Peran Unit Patroli Satuan Sabhara Dalam Mencegah Tindak Pidana Pencurian Dengan Pemberatan - Aditya Sakti Yudobhakti (Police Studies Review, 2020)
The backround of this research is that criminal acts of theft with burdens are rampant in Bogor City Polresta and included in prominent cases the role of the Sabhara Unit Patrol in the framework of preventing theft with burdens and inhibitor faced by the Sabhara Unit Patrol in preventing the crime of theft burdens. In this research the author uses 2 theories that are, the theory of “Management”, the theory of “routine activities”. The author also uses 3 concepts in writing this paper, that are the concept “Patrol”, the concept of “Sabhara”, the concept of “Role”. This study uses a qualitative approach with descriptive analysis methods and data collection techniques using observation techniques, interview techniques, and literature study techniques. Data sources come from primary data sources, secondary data sources, and tertiary data sources. The results of research and discussion, that the crime of theft by burdens in Bogor City is doing by 3 kind of operand mode. The role of the Patrol Unit is to conduct patrols, the submission of public order and tips to prevent theft by burdens. The obstacles faced are divided into internal and external constraints. The conclusions in this thesis are: (1) theft by burdens in Bogor City (2) prevention of theft by burdens has not been maximally implemented, (3) obstacles which encountered include patrol units concurrently with VVIP security duties, different language styles, there are members who have not doing Dikbangspes, lack of awareness from the community, and many residents who work outside the city of Bogor. Suggestions from the author are that improvements of competencies should be made to the Bogor City Police personel, the patrol unit was not involved in securing VVIP, and additional efforts were made especially on weekends.